Political affiliation and willingness-to-pay for publicly versus privately provided environmental goods - Ian Bateman; Diane Dupont (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
Previous literature has found that politically conservative individuals express a lower willingness-to-pay (WTP) for environmental goods than left-wing supporters. Using data from three surveys valuing water we investigate the role of context by evaluating whether the means of provision (public or private) matters. While left-wing voters have higher WTP for publically provided public goods, right-wing voters have a higher WTP when a good is privately provided. Our findings have implications for values typically obtained for environmental public goods using survey data from constructed markets since scenarios typically describe improvements as being publically provided.
Keywords: 330; Stated preference; public provision; private provision; valuation; political affiliation; water; Umweltpolitik; Umweltschutz; Umweltverträgliches Produkt; Privatwirtschaft; Öffentlicher Sektor; Wahlverhalten; Willingness to pay